cMYC expression in thyroid follicular cell-derived carcinomas: a role in thyroid tumorigenesis - Hany I. Sakr; Deborah J. Chute; Christian Nasr; Charles D. Sturgis (BMC, 2017)
Abstract Background cMYC regulates approximately 15% of human genes and is involved in up to 20% of all human cancers. Reports discussing cMYC protein expression in thyroid carcinomas are limited, with controversies pertaining to cMYC expression patterns noted in the literature. The aims of the current study were to clarify patterns and intensities of cMYC expression in follicular cell-derived thyroid carcinomas across a spectrum of cancer morphologies and disease aggressivities, to correlate cMYC with BRAFV600E expression, and to evaluate the potential role of cMYC in progression of well-differentiated thyroid carcinomas into less well-differentiated carcinomas. Methods Immunohistochemical studies using specific monoclonal antibodies for cMYC and BRAFV600E were performed on tissue microarrays built from follicular cell-derived thyroid carcinomas (25 papillary, 24 follicular, 24 oncocytic variant of follicular, and 21 undifferentiated). In addition, cMYC IHC testing was also performed on whole tissue tumor sections from a subset of patients. Nodular hyperplasia cases were used as non-neoplastic controls. Appropriate positive and negative controls were included. Results cMYC was expressed almost exclusively in a nuclear fashion in both thyroid carcinomas and nodular hyperplasias. cMYC expression was weakly positive in both nodular hyperplasias and well-differentiated carcinomas. The majority of undifferentiated carcinomas (UDCs) showed strong nuclear cMYC positivity. PTC cases that were positive for cMYC (6/25) harbored the BRAF V600E mutation. A correlation was confirmed between cMYC intensity and tumor size in UDCs. UDC cases that developed out of well-differentiated thyroid carcinomas showed frank overexpression of cMYC in the undifferentiated tumor components. Conclusions Our study suggests that nuclear overexpression of cMYC correlates with tumorigenesis / dedifferentiation in follicular cell derived thyroid carcinomas, a concept that has not been shown before on whole tissue sections.